Left Main Coronary Artery Ostial Repair with Autologous Ring‐Shaped Aortic Patch for Iatrogenic Aortic Dissection. Issue 6 (1st October 2014) - Barbero, Cristina; Di Rosa, Elio; Devotini, Roger; Attisani, Matteo; Rinaldi, Mauro
Abstract: Iatrogenic left main coronary artery and aortic root dissection are rare complications during coronary catheterization. A case of catheter‐induced left main coronary artery dissection with subsequent retrograde progression into the ascending aorta wall is reported. The patient was surgically managed with an ascending aorta replacement and left coronary ostial repair with an autologuos aortic wall ring‐shaped patch in the paraostial position in order to seal the intimal tear. doi: 10.1111/jocs.12446 (J Card Surg 2014;29:821–823)